IDENTIFICATION OF DEFECTS OF PET AND HDPE-BASED DRINKING WATER PACKAGING PRODUCTS - S Pupon; M Nugraha; Y Febryani; RS Tasnim; U Lestari; A Sarmada (Jurnal Ilmiah Publipreneur, 2020)
Increased community mobility has an impact on increasing demand for packaged beverage products. Data from Aspadin (the association of bottled water companies) there are more than 1500 brands of bottled water (AMDK) in Indonesia and it is estimated that trade will continue to increase every year. However, the profit margins of bottled drinking water products are not classified as high, so producers must do efficiency. One form of efficiency that can be done is to reduce the waste of packaging production, where most bottled water is made of plastic. This study aims to identify several product defects that often occur during the production process of bottled water based on PET. The process of making plastic-based drinking water packaging is divided into 3 stages. First is to make a bottle preform, the second is the blow molding process, which is the process of making a whole package from a preform, and the third is the process of making a lid. The machines used in these stages are different and in each of the stages successfully classified types of product defects. During the preform manufacturing stage, black specks or contaminants, short shots, bubbles, and flash are found. At the stage of making the whole bottle includes, off center base, failed blowing, arising bracelet, rough parting line. The last defect in the process of making the cap includes excess material flash Short shot, bridge or ring break, leak centergate.